2022
DOI: 10.1007/s00421-022-05047-6
|View full text |Cite
|
Sign up to set email alerts
|

Ratings of perceived exertion from a submaximal 20-m shuttle run test predict peak oxygen uptake in children and the test feels better

Abstract: Purpose To determine the validity and test–retest reliability of using ratings of perceived exertion (RPE) elicited during a submaximal 20-m Shuttle Run Test (20mSRT) to predict VO2peak in children and investigate acute affective responses. Methods Twenty-five children (14 boys; age, 12.8 ± 0.7 years; height, 162.0 ± 9.3 cm; mass, 49.9 ± 7.7 kg) completed four exercise tests (GXT, 2 submaximal 20mSRT, maximal 20mSRT). The Eston–Parfitt RPE scale was used, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Instead, HRmax was approximated with a formula, which is recommended in cases when HRmax cannot be measured with appropriate tests (23). Nevertheless, measuring HRmax is recommended for future studies, for example, with a 20 m shuttle run test (6), which is a widely used test in soccer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, HRmax was approximated with a formula, which is recommended in cases when HRmax cannot be measured with appropriate tests (23). Nevertheless, measuring HRmax is recommended for future studies, for example, with a 20 m shuttle run test (6), which is a widely used test in soccer.…”
Section: Discussionmentioning
confidence: 99%
“…Yelling et al (4) described lower correlations in eleven-and twelve-compared to fourteen-and fifteen-year-olds. Conversely, other studies found large and excellent correlations between RPE and HR or performance measures already in nine-and twelve-year-olds (5,6). Thus, several factors appear to influence how well children can rate perceived effort.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This makes it particularly important to tailor physical activity recommendations not only to a patient's pain level, but to other factors that may limit physical abilities, such as excess weight [6]. One way to develop appropriate physical activity interventions for youth with chronic pain is to account for each patient's fitness level, training load, and exercise intensity through the assessment of perceived exertion [7][8][9][10]. Unfortunately, there are no existing pediatric scales validated for youth with chronic pain.…”
Section: Introductionmentioning
confidence: 99%